Sustainable consumption knowledge and practices of Kansans: An exploration of accuracy and depth of understanding - LeHew, Melody (Kansas State University, 2009)
The proposed presentation will report the preliminary results from Phase 1 of an extended research project focused on examining ecologically sustainable consumption practices. A qualitative methodology was used in this phase to develop a better understanding of self-identified sustainable consumers and the life experiences and motivations driving their sustainability practices. The key objectives were to assess participants understanding of sustainability, to explore their current sustainability behavior and whether apparel-related sustainable consumption was included in their portfolio of practices The well-being of individuals, families and organizations is dependent upon responsible consumption of world resources. The human ecology approach focuses on holistic understanding of the interconnectedness of our economy and world, which is compatible with a sustainability perspective. Sustainability can be defined as making decisions regarding satisfaction of needs of today without endangering/limiting the satisfaction of our future generation’s needs. It is a long-term view that encourages responsible and ethical use of the world’s resources. The United States, while the greatest consumer of resources, has not been as proactive regarding conservation as other developed countries. Although we have been slow to adopt sustainability in an overt or government sponsored sense, Cohen, Comrov, and Hoffner (2005) suggest that there is a new and growing politics of consumption occurring among the U.S. citizenship. A collection of separate movements can be identified by three categories: (1) social and political protest campaigns, (2) lifestyle reinventions, and (3) public policy initiatives (Cohen, Comrov, & Hoffner, 2005, p. 2). For this study, recruitment flyers and newspaper advertisements were used to find individuals self-identifying themselves as a participant in one of the lifestyle reinvention movements (i.e. Voluntary Simplicity, Slow Food, Ethical Consumption). Focus group interviews were used to discuss personal characteristics (life experience, values, etc.) that influenced these consumers. The interview method was selected to extract a deeper level of understanding than may result from utilizing only a standardized questionnaire. Preliminary data analysis suggests participants predominantly define sustainability as the responsible use of resources and protection of the environment. There were varying degrees of commitment to sustainable consumer behavior, as well as a variety of factors motivating these Kansans to become more sustainable. Some motivational factors discussed included: a connection to nature, being raised on a farm, religious values, and influence of one’s family. Participants also discussed barriers to becoming more sustainable, with lack of local services, the inconvenience or lack of incentives, and the lack of education and role models as some of the key impediments identified. Another interesting facet revealed was that respondents could easily make the connection between sustainability and food consumption practices as well as recycling of materials after use, but were less clear about the link between sustainability and apparel consumption behavior. Cohen, M. J., Comrov, A., & Hoffner, B. (2005). The new politics of consumption: Promoting sustainability in the American marketplace. Sustainability: Science, Practice, & Policy [http://ejournal.nbii.org], 1(1), 1-19.
Keywords: Consumption; Sustainability; Consumer knowledge; Consumer behavior; Voluntary simplicity; Slow philosophy; Ethical consumption